(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the essential role of reading instruction in fostering critical thinking skills within the English classroom. It begins by establishing the significance of critical thinking in modern education and emphasizes its alignment with the goals of English language teaching. Throughout the text, the author(s) delve into the relationship between reading comprehension and critical thinking, highlighting how active engagement with texts can stimulate higher-order thinking processes. Various strategies for developing critical thinking during reading instruction are discussed, including questioning techniques, text annotation, classroom discussions, critical reading strategies, Socratic questioning, problem-solving tasks, and writing assignments.